IMPACTO DO CONFLITO INTRAGRUPAL, DO SUPORTE SOCIAL NO TRABALHO E DO AUTOCONCEITO PROFISSIONAL SOBRE A RESILIÊNCIA: UM ESTUDO COM POLICIAIS MILITARES. - Emilio, Eduarla Resende Videira (2011)
Resilience is a construct that refers to the ability of human beings to successfully face the adversities of life, overcome them and even be strengthened or changed by them. Fields of psychology research, such as Health Psychology, Positive Psychology and Positive Organizational Behavior, have considered the resilience as an important way to understand the positive and healthy aspects of human beings. This work aims to expand knowledge about the resilience and their relations with other constructs in the organizational context. For this, the objective of this research was to verify the predictive capacity of intragroup conflict (relationship and task), of social support at work (emotional, informational and instrumental) and of professional self-concept (health, realization, self-confidence and competence) on resilience (positive adaptation or acceptance of change, spirituality, resignation towards life, personal competence and persistence in the face of difficulty) of military police. The study included 133 military police officers of a battalion in the state of Sao Paulo, prevailing male subjects (97.7%), mean age 30 years (SD = 5.7). The following scales were used to measure the variables:Resilience Rating Scale reduced, Intragroup Conflict Scale, the Scale of Perceived Social Support at Work and Self-Concept Scale. The data were submitted to descriptive calculations and at analyses of multiple lineal regression standard. The results indicated that the model that grouped the antecedent variables (intragroup conflict, social support at work and professional selfconcept) significantly explained the variance of the dimensions of resilience: 30% of persistence in the face of difficulties, 29% of positive adaptation or acceptance of change, 28% of personal competence and 11% of spirituality. Variables that were statistically significant impact on persistence in the face of difficulties were emotional support at work, whose direction of the prediction was opposite, and confidence, whose direction of prediction was direct. Positive adaptation or acceptance of change was as inverse predictor the health and as direct predictor the self-confidence. The personal competence had a significant impact on the variable selfconfidence, wich was a direct predictor. Spirituality, in turn, had a single significant predictor, the variable realization, whose direction of prediction was direct. The results suggest that among the independent variables, the professional self-concept demonstrated greater explanatory power of the variance in resilience. In light of the theory of the area were discussed these findings. Finally,limitations and the suggestion a research agenda that confirm and expand the results of this research were presented.